ANALISIS PELAKSANAAN TES KEMAMPUAN AKADEMIK (TKA) MATA PELAJARAN MATEMATIKA BAGI SISWA KELAS IX SMP AL-WILDAN ISLAMIC SCHOOL 14 BUMI MUTIARA - Ul’fah Hernaeny; Abdul Azis; Ahmad F. Abdulrasyid; Risti Ayu Tirtasari; Rani Alvama Dewi; Calista Mega Septiani; Asep Maolana A (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The implementation of learning evaluation, particularly through the Academic Ability Test (TKA), is important for comprehensively measuring students’ abilities, especially in Mathematics, which requires logical thinking and problem-solving skills. However, in practice, students’ readiness in facing the TKA is still not fully optimal, as indicated by a gap between the expected academic competence and the actual conditions found in the field, particularly in terms of learning strategies, mastery of material, and psychological aspects during the test. This condition highlights the need for an in-depth study of students’ preparation, experiences, and challenges in implementing the TKA. This study aims to analyze the preparation, experiences, and challenges faced by Grade IX students in the implementation of the Mathematics TKA. This research uses a descriptive quantitative approach with a Likert-scale questionnaire administered to 62 students. The data were analyzed using descriptive statistics, including mean, percentage, and frequency distribution. The results show that students have a fairly good level of preparation, indicated by study habits, practice exercises, and efforts to understand the material before the test. Students’ experiences during the TKA implementation were also generally positive, particularly in terms of understanding instructions and exam conditions. However, several challenges were still identified, including time limitations, difficulties in understanding questions, and anxiety during the test. The conclusion of this study shows that although the implementation of the TKA has gone relatively well, improvements in students’ academic readiness and psychological management are still needed to ensure more optimal evaluation results that truly reflect students’ overall academic abilities. ABSTRAK Pelaksanaan evaluasi pembelajaran, khususnya melalui Tes Kemampuan Akademik (TKA), menjadi penting dalam mengukur kemampuan siswa secara komprehensif, terutama pada mata pelajaran Matematika yang menuntut kemampuan berpikir logis dan pemecahan masalah. Namun, dalam praktiknya masih ditemukan bahwa kesiapan siswa dalam menghadapi TKA belum sepenuhnya optimal, ditandai dengan adanya kesenjangan antara kemampuan akademik yang diharapkan dengan kondisi nyata siswa di lapangan, terutama terkait strategi belajar, penguasaan materi, serta aspek psikologis saat menghadapi tes. Kondisi ini menunjukkan perlunya kajian yang lebih mendalam mengenai bagaimana persiapan, pengalaman, dan kendala siswa dalam pelaksanaan TKA. Penelitian ini bertujuan untuk menganalisis persiapan, pengalaman, dan kendala yang dihadapi siswa kelas IX dalam pelaksanaan TKA mata pelajaran Matematika. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan instrumen berupa kuesioner skala Likert yang diberikan kepada 62 siswa. Data dianalisis menggunakan statistik deskriptif yang meliputi rata-rata, persentase, dan distribusi frekuensi. Hasil penelitian menunjukkan bahwa siswa memiliki tingkat persiapan yang tergolong baik melalui kebiasaan belajar, latihan soal, dan upaya memahami materi sebelum tes. Pengalaman siswa selama pelaksanaan TKA juga cenderung positif, terutama pada aspek pemahaman instruksi dan kondisi pelaksanaan ujian. Namun demikian, masih ditemukan kendala berupa keterbatasan waktu, kesulitan memahami soal, serta kecemasan saat mengerjakan tes. Kesimpulan penelitian ini menunjukkan bahwa meskipun pelaksanaan TKA berjalan cukup baik, peningkatan kesiapan akademik dan pengelolaan faktor psikologis siswa masih diperlukan agar hasil evaluasi lebih optimal dan benar-benar mencerminkan kemampuan akademik siswa secara menyeluruh.